PENDIDIKAN KARAKTER DI INDONESIA DALAM TINJAUAN PSIKOLOGIS - Noormawanti Noormawanti (Universitas Muhammadiyah Metro, 2017)
Character education can be interpreted simply form the character, temperament, character and personality of a person by instilling noble values, so the values are ingrained, united in heart, mind, word and deed and showed its influence in the reality of life is easy, on his own, original and as sincere for Allah alone. Planting and personality formation was carried out not only by giving understanding and change mindsets and patterns of view of someone about something that is good and true, but good values are socialized, trained, exemplified, performed continuously and practiced in the daily lives day.Psychologically humans are per se there are various psychological tendencies or dislike something. Psychologically man happy about new things, funny and intriguing. Besides humans also have the feeling of wanting to be appreciated, wanted company, want to be praised, to be given a gift or something and so forth. Thus the human psychological state that it should be used as a door to instill the values of character education. The tendency of human psychology so it has been responded to and used by the Qur'an carefully in instilling the values of character education. Key Words : Education, Character, psychologi